Differences in healthcare costs in youths with conduct disorders in rural vs. urban regions: an analysis of German health insurance data - Heike Gerhardt; Monika Heinzel-Gutenbrunner; Christian J. Bachmann (BMC, 2018)
Abstract Background For children and adolescents with mental health problems, there is a lack of data as to whether the type of residential area (urban vs. rural) influences healthcare costs for affected individuals. The aim of this study was therefore to explore potential urban vs. rural healthcare cost differences in children and adolescents with conduct disorder (CD), one of the most frequent and cost-intensive child and adolescent psychiatric disorders. Additionally, we aimed to compare healthcare costs of youths with CD, and of youths without this diagnosis. Methods We analysed data from a German health insurance company, extracting all youths with a CD diagnosis in 2011 (CD group; N = 6337), and an age- and sex-matched group without this diagnosis (control group). For both groups, annual costs per person for outpatient and inpatient healthcare were aggregated, stratified by area of residence (urban vs. rural). Results While mean annual overall costs in the CD group did not differ significantly between urban and rural areas of residence (2785 EUR vs. 3557 EUR, p = 0.253), inpatient treatment costs were significantly higher in rural areas (2166 EUR (60.9% of overall costs) vs. 1199 EUR (43.1% of overall costs), p < 0.0005). For outpatient healthcare costs, the reverse effect was found, with significantly higher costs in individuals from urban areas of residence (901 EUR (32.3% of overall costs) vs. 581 EUR (16.3% of overall costs), p < 0.0005). In the control group, no significant rural vs. urban difference was found for either overall health costs, inpatient or outpatient costs. Mean overall costs in the CD group were four times higher than in the control group (3162 (±5934) EUR vs. 795 (±4425) EUR). Conclusions This study is the first to demonstrate urban vs. rural differences in healthcare costs among youths with CD. The higher costs of inpatient treatment in rural regions may indicate a need for alternative forms of service provision and delivery in rural settings.